Cinnamomum cassia Presl flavonoids prevent hyperglycemia-induced cognitive impairment via inhibiting of AGEs accumulation and oxidative stress. (January 2023) - Li, Hemei; Zhou, Jinling; Liu, Sitong; Chen, Xiuting; Qin, Tiantian; Huang, Guodong; Luo, Peizhen; Hu, Ying; Xia, Xing
Graphical abstract: Highlights: Cinnamomum cassia Presl flavonoids ( CFS) prevented diabetes-induced cognitive impairment in rats. CFS alleviated the hippocampal morphology damage and oxidative stress in the rats. CFS decreased AGEs formation both in vitro and in the hippocampus. AGEs-RAGE pathway was deactivated by CFS in diabetic rats. Abstract: Cinnamomum cassia Presl (CCP) has a beneficial impact on diabetes and dementia. In this research, the underlying mechanism of flavonoids of Cinnamomum cassia Presl (CFS) on diabetes-related cognitive impairment (DRCI) were inferred by a network pharmacology approach. The conjectures of network study were verified through the advanced glycation end products (AGEs) systems in vitro and the long-term diabetic rats. The experimental results showed CFS inhibited AGEs generated from nonenzymatic glycosylation reaction in vitro as well as in the brain of long-term diabetic rats in a dose-dependently manner. In morris water maze study, CFS restored the cognitive ability of diabetic rats. Moreover, the hippocampal morphology damage and oxidative stress were ameliorated by CFS, while the hippocampal level of AGEs, RAGE and pJNK/JNK were decreased significantly. These results indicated CFS may suppress AGEs accumulation via inhibiting glycosylation, and alleviating oxidative stress caused by AGEs, thereby prevents the neuronal injury and ameliorates DRCI.